Spare Parts and Design Protection – Different Approaches to a Common Problem. Recent Developments from the EU and US Perspective. Issue 7 (2nd July 2020) - Beldiman, Dana; Blanke-Roeser, Constantin; Tischner, Anna
Abstract: The market for auto spare parts is of major significance to the national economies of countries with automotive industries. Because original manufacturers (OEMs) hold design protection over spare parts, they tend to monopolize the spare parts aftermarket to the exclusion of third-party producers of replica parts. Spare parts producers argue for liberalization of the market. Governments in spare-part producing countries have been open to this approach, whereas most countries with strong automotive industries have so far rejected it. However, at least on the EU front, the legal debate on whether and how to effect this liberalization, which has been ongoing for almost two decades, is getting closer to a resolution. The German legislator will soon insert a repair clause into the national DesignG on the basis of Art. 14 Design Directive. The new Sec. 40a DesignG will come into force within the first half of 2020 and will be applicable only to designs registered from that point on. The scope of the clause will be limited to form-dependent (i.e. especially must match) parts. This article compares the evolution of the EU position regarding spare parts, including the German draft, and the criticism it received among scholars, to the evolution of the spare parts situation in the US.